2022
DOI: 10.1186/s12967-022-03642-x
|View full text |Cite
|
Sign up to set email alerts
|

Omentin1 ameliorates myocardial ischemia-induced heart failure via SIRT3/FOXO3a-dependent mitochondrial dynamical homeostasis and mitophagy

Abstract: Background Adipose tissue-derived adipokines are involved in various crosstalk between adipose tissue and other organs. Omentin1, a novel adipokine, exerts vital roles in the maintenance of body metabolism, insulin resistance and the like. However, the protective effect of omentin1 in myocardial ischemia (MI)-induced heart failure (HF) and its specific mechanism remains unclear and to be elucidated. Methods The model of MI-induced HF mice and oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…In contrast, in BMAL1 deficient hESC-derived cardiomyocytes, impaired mitophagy is a key cause for the development of dilated cardiomyopathy [60]. In Hu's study, constructing mice with overexpression of omentin1 demonstrated that omentin1 activated mitophagy to improve HF [61]. In cardiac ischemia-reperfusion injury associated with disturbed mitochondrial homeostasis, the casein kinase 2α amplifies cardiomyocyte death signals by inhibiting mitophagy [62].…”
Section: Mitophagy Damage In Cvdsmentioning
confidence: 99%
“…In contrast, in BMAL1 deficient hESC-derived cardiomyocytes, impaired mitophagy is a key cause for the development of dilated cardiomyopathy [60]. In Hu's study, constructing mice with overexpression of omentin1 demonstrated that omentin1 activated mitophagy to improve HF [61]. In cardiac ischemia-reperfusion injury associated with disturbed mitochondrial homeostasis, the casein kinase 2α amplifies cardiomyocyte death signals by inhibiting mitophagy [62].…”
Section: Mitophagy Damage In Cvdsmentioning
confidence: 99%
“…Foxo3a is a transcription factor that essential for cell survival and stress response, which involved in various cellular processes, including apoptosis and mitochondrial dynamics (28). Emerging evidence have demonstrated that Parkin interact with Foxo3a to coordinate mitochondrial dynamics, enhance mitochondrial quality control, and suppress cell apoptosis (42,43). In this study, we found Foxo3a blinds to Parkin and regulates the expression of Parkin protein.…”
Section: Discussionmentioning
confidence: 99%
“…This further promotes the release of cytochrome C and apoptotic factors, thereby mediating changes in mitochondrial dynamics and inducing myocardial cell apoptosis. [23] Consequently, manipulating mitochondrial dynamics plays a crucial role in controlling…”
Section: Regulatory Mechanisms Of Mitochondrial Dynamics In Hf Differ...mentioning
confidence: 99%